ANALYSIS OF IMPROVING STUDENT LEARNING OUTCOMES IN SCIENCE LEARNING PHOTOSYNTHESIS MATERIALS FOR CLASS IV PAYA DUA STATE ELEMENTARY SCHOOL USING THE PjBL MODEL - Faisal Muadi; Lili Kasmini; Siti Mayang Sari (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
This study aims to examine the application of the PjBL model in improving student learning outcomes on photosynthesis. The research subjects were 36 students in class IV of Paya Dua Public Elementary School for the academic year 2022/2023. This research is qualitative research, which focuses on a deeper understanding of the phenomenon being studied, in this case the use of the PjBL model in improving student learning outcomes. The research results show that the implementation of PjBL can improve student learning outcomes. It can be shown that the average mastery score before using the PjBL model was 49.36 and increased after using the PjBL model, namely reaching 67.91. Student learning outcomes increased by 18.55 from before and after using the PjBL model. However, even though there has been an increase, student learning outcomes are still below the Minimum Completeness Criteria score of 70. So it can be concluded that the PjBL model is believed to be effective and has a positive effect on learning that is able to improve student learning outcomes in photosynthesis material in fourth grade students of Paya Dua public elementary school, but from the results of the analysis, the increase in students still has not reached the Minimum Completeness Criteria score of 70. Thus, it is necessary to carry out follow-up actions to address the problem, so that the average student learning outcomes can reach the Minimum Completeness Criteria value in science learning for Grade IV elementary school students’ country of Paya Dua.